EFEKTIVITAS PPL UNTUK MENINGKATKAN EFIKASI DIRI MENGAJAR PADA MAHASISWA PENDIDIKAN MATEMATIKA - Aji Cokro Dewanto (Universitas Pekalongan, 2018)
Most students consider mathematics is a difficult subject, and it becomes a challenge for the teachers to teach the subject in a good way. Therefore, future mathematics teachers need self-efficacy in teaching the subject. This research aims to find out the effectivity of field experience practice to increase teaching self-efficacy in 15 students of Mathematics Education Program, Teaching and Education Departement of Universitas Pekalongan, Semester VII 2017/2018 period. This research implemented experiment method with the one group pretest-posttest design. Teaching self-efficacy variable was measured by Teaching Self-Efficacy Scale which was tested to 105 students of Teaching and Education Departement Universitas Pekalongan semester VII, the result of aplha croncbach reliability coefficient was 0,966. This research showed a significant increase in teaching self-efficacy mean for 23,76%, with the significance of 0,001 (p<0,05). Further analysis for the aspects of teaching self-efficacy showed that magnitude aspect was increase for 26,73% (p<0,05) generality aspect was increase for 26,73% (p<0,05), and strength aspect was increase for 26,73% (p<0,05). In conclusion, field experience practice could significantly increase teaching self-efficacy of mathematics education students.